Elasto-plastic analysis of functionally graded metal-ceramic beams under mechanical loading - Kien, Nguyen Dinh; Thom, Tran Thi; Alexandrov, Sergey; Ha, Le Thi (Vietnam Journal of Mechanics, 2017)
The elasto-plastic analysis of functionally graded (FG) metal-ceramic beams under mechanical loading by using the finite element method is presented. A bilinear stress-strain relation with isotropic hardening is assumed for elasto-plastic behaviour of metal, and the effective elasto-plastic properties of the functionally graded material are evaluated by using Tamura-Tomota-Ozawa (TTO) model.  A nonlinear beam element based on the classical beam theory is formulated and employed in the analysis. The element employed nonlinear von Kámán strain-displacement relationship is derived by using the neutral surface as reference plane. The layer beam approach, in which the plastic rate equation is solved at Gauss points,  is adopted in updating the stress and evaluating the element nodal force vector and tangent stiffness matrix. Numerical examples are given to show the accuracy of the derived formulation and to illustrate the effect of the material distribution and plastic deformation on the behavior of the beams. The formation and propagation of plastic zone during the loading process is also examined and highlighted.